Antecedents and influence of social media influencers' credibility on brand attitude: findings from PLS-SEM and NCA - Kin Leong Tang; Hooi Rae; Pei Meng Tan; Tan Suk Shiang; Chong Zee Ting Stephnie (Penerbit Universiti Kebangsaan Malaysia, 2025)
Nowadays, it is common to engage social media influencers (SMIs) in social marketing to promote brands and products. Nevertheless, the effect of influencer marketing in Malaysia, especially the credibility of SMIs and its impact on brand attitude, has not been subject to much discussion. Therefore, the goal of this study is to examine the antecedent credibility of SMIs in social media marketing campaigns, which leads to brand attitude, particularly among Malaysian Generation Y and Z. This study targeted Generation Y and Z in the Klang Valley, Malaysia. An online survey was conducted using convenience and purposive sampling techniques. The collected data were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM) technique, followed by Necessary Condition Analysis (NCA) to determine the critical factors that contribute to the outcome. The PLS SEM estimation results show that similarity, expertise, likeability, argument quality and trustworthiness significantly influence SMIs' credibility, which in turn affects the positive brand attitude. The NCA results also suggest that these factors are significant contributors to credibility. Notably, both argument quality and likeability are two factors that have a large effect on credibility. This study adds to the body of knowledge to assist a better understanding of the antecedent influence of credibility and to confirm the significant factors which contribute to credibility, leading to brand attitude. Methodologically, PLS-SEM and NCA approaches were used in this study to confirm the hypotheses. From a managerial perspective, this study offers several strategies to build the credibility of influencers and promote business sustainability through brand attitude.